2017
DOI: 10.3389/fncir.2016.00115
|View full text |Cite
|
Sign up to set email alerts
|

Breathing as a Fundamental Rhythm of Brain Function

Abstract: Ongoing fluctuations of neuronal activity have long been considered intrinsic noise that introduces unavoidable and unwanted variability into neuronal processing, which the brain eliminates by averaging across population activity (Georgopoulos et al., 1986; Lee et al., 1988; Shadlen and Newsome, 1994; Maynard et al., 1999). It is now understood, that the seemingly random fluctuations of cortical activity form highly structured patterns, including oscillations at various frequencies, that modulate evoked neuron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
184
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(206 citation statements)
references
References 98 publications
(109 reference statements)
9
184
0
Order By: Relevance
“…In humans, the continuous, involuntary rhythm of breathing is generated within the brainstem 49 , however, very little is known about the conscious control of breathing 24 . This study demonstrates a role for the amygdala in voluntary respiratory control and allows for further study of this pathway in dysfunctional breathing states - not only in those with epilepsy but also infants with developmental abnormalities and in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the continuous, involuntary rhythm of breathing is generated within the brainstem 49 , however, very little is known about the conscious control of breathing 24 . This study demonstrates a role for the amygdala in voluntary respiratory control and allows for further study of this pathway in dysfunctional breathing states - not only in those with epilepsy but also infants with developmental abnormalities and in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the authors suggest crossfrequency coupling to involve neural interactions between premotor areas and both insular and cingulate cortex as well as the medulla, which is precisely the pathway we propose to connect deep and cortical nodes within the RMBO network. A simple graph model of excitatory and inhibitory cells has been shown as proof of principle for cortical gamma modulation through respiration (modelled as sinusoidal input) 45 . The authors later concluded that respiration-locked brain activity has two driving sources 46 : On the one hand, respiration entrains OB activity via mechanoreceptors (i.e., phase-phase coupling), as seen in LFP 23 .…”
Section: Potential Mechanisms Behind Rmbosmentioning
confidence: 99%
“…Although most research has focused on the cardiovascular system, the respiratory rhythm is a strong candidate to bridge the gap between brain and body during emotion. Breathing is strongly modulated during fear and other emotions (14,15) and numerous studies have shown that the respiratory rhythm can influence neuronal dynamics, mainly via feedback from the olfactory system (16), in many brain areas such as the hippocampus, amygdala and prefrontal cortex in both rodents (17)(18)(19)(20) and humans (21). We hypothesized that breathing is therefore a marker of emotional state poised to directly impact neuronal functioning in the cortical and limbic system to regulate fear expression (FigS1).…”
Section: Main Textmentioning
confidence: 99%